Degradation Analysis of Grid Interfaced Solar Pv Plant in Coastal Climate Conditions - Sagiraju Dileep Kumar Varma; Koduri Omkar; S. M. Padmaja; SSSR Sarathbabu Duvvuri; Srikanth M V (Journal of Renewable Energy and Environment)
Solar photovoltaic (PV) plants experience performance degradation due to environmental, operational, and material factors. Therefore, conducting a degradation analysis is essential to ensure the optimal performance and longevity of a solar PV plant. The main objective of this study is to investigate the impact of degradation on solar panels in various abnormal scenarios by evaluating performance indicators and electrical parameters of the PV plant. The core novelty of this research lies in the development of an integrated real-time degradation analysis framework for grid-interfaced solar PV plants, using both an I-V curve tracer and a thermal image camera in abnormal scenarios. This approach provides a comprehensive and precise assessment of the PV system's health by capturing detailed electrical characteristics and identifying thermal anomalies indicative of degradation. The key findings include the evaluation of electrical parameters and performance indicators such as peak power (Pmax), short-circuit current (Isc), open circuit voltage (Voc), Performance Ratio (PR), Fill Factor (FF), and the annual power degradation rate in various abnormal scenarios. An error analysis for all electrical parameters of the PV plant was conducted, comparing the percentage errors for each parameter with the panel parameters measured under standard test conditions. Finally, the performance metrics of the current study were compared with previous literature.